Hubungan Penggunaan Gadget dengan Perkembangan Kognitif dan Sosial Anak di TK Aisyiyah Bustanul Athfal 09 Sidayu - Puspita Maharani, Laras; Lita Fitrianur, Widya; Fauziah Zuhro, Diah; Suminar, Ervi (Jurnal Stunting Pesisir dan Aplikasinya, 2025)
Children at an early age are often exposed to gadgets without supervision which can cause addiction, decreased thinking abilities and impaired social interaction. This research aims to analyze the relationship between gadget use and children's cognitive and social development. This research uses a quantitative design with a cross-sectional approach. The sample consisted of 88 children selected randomly using simple random sampling techniques. Data was collected through questionnaires on gadget use and social development as well as observations of cognitive development. Data analysis used the Spearman Rank test. The results of research at Kindergarten Aisyiyah Bustanul Athfal 09 Sidayu were that most of the use of gadgets was in the medium category as many as 45 (51.1%) children, cognitive development was mostly in the beginning to develop category as many as 52 (59%) children and social development was in the doubtful category as many as 48 (51.1%) children. The use of gadgets with children's cognitive development obtained a p value of 0.000 <0.05. The results of research on gadget use and children's social development showed a p value of 0.000 < 0.05. There is a relationship between gadget use and children's cognitive and social development at Aisyiyah Bustanul Athfal 09 Sidayu Kindergarten